Pers Negara Bertetangga - Prajarto, Nunung (Jurnal Ilmu Sosial dan Ilmu Politik, 1998)
(Press Between Two Neighbouring Countries) Cultural differences between the Indonesian and Australian media sometimes create complaints and tensions. While the Australian media are generally regarded as being aggressive, fond of conflict, eager to get to the core of issues quickly and playing "supervisory" role, the Indonesian media are portrayed as being governments microphone and leaving the fact and the truth. The problem to be discussed centre on how the various views of the neighbouring countries press emerge. By brushing aside the reasons to rationalise and the existed opinions, this paper shows that both the Indonesian and Australian press have implemented a good professional standard of journalism.